1990
DOI: 10.1002/clc.4960130711
|View full text |Cite
|
Sign up to set email alerts
|

Improved diastolic LV filling after acute application of ajmaline in patients with coronary artery disease and normal systolic LV function

Abstract: Summary: To determine whether ajmaline (A) can be safely applied in coronary artery disease (CAD), changes of left ventricular (LV) function after acute ajmaline application were analyzed by pulsed Doppler echocardiography in 10 CAD patients. LV pressures in systole and end-diastole and LVEF remained normal and comparable. Doppler normalized peak filling rate (p<0.02), peak early/atrial filling velocity (E/A) ratio (peO.01) and Edeceleration (pe0.05) increased. The increase in E/A and in E-deceleration relativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1993
1993
2000
2000

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Ajmaline administration was well tolerated, as it has little or no effect on the left ventricular function [5, 8]. The regular indications for ajmaline are the assessment of patients with Wolff-Parkinson-White syndrome, Brugada syndrome and bifascicular block, as well as the termination of supraventricular and ventricular tachyarrhythmias [9, 10, 11, 12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Ajmaline administration was well tolerated, as it has little or no effect on the left ventricular function [5, 8]. The regular indications for ajmaline are the assessment of patients with Wolff-Parkinson-White syndrome, Brugada syndrome and bifascicular block, as well as the termination of supraventricular and ventricular tachyarrhythmias [9, 10, 11, 12, 13].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that in the clinical study of Kleinsorge, ajmaline was reported to have positive inotropic effect (59,75,78). Huting et al (67) showed no adverse hemodynamic effects of ajmaline in patients with preserved left ventricular function.…”
Section: Prajmalium In the Treatment Of Cardiac Arrhythmiasmentioning
confidence: 99%